2008
DOI: 10.2337/dc07-2449
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Diabetes and Polychlorinated Biphenyls and Dioxins

Abstract: OBJECTIVE -Polychlorinated biphenyls (PCBs) and polychlorinated dibenzofurans (PCDFs) are important and persistent organic pollutants (POPs) in humans. Recent cross-sectional studies have detected increased concentrations of serum POPs in diabetic patients. We aimed to examine the association between previous high exposures to PCBs and PCDFs and the cumulative incidence of type 2 diabetes and hypertension.RESEARCH DESIGN AND METHODS -During the late 1970s, the consumption of rice-bran oil laced with PCBs poiso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
130
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(164 citation statements)
references
References 29 publications
16
130
2
2
Order By: Relevance
“…The Michigan PBB study (25 years of follow-up) showed increased incidence of diabetes in individuals with a PCB level >10.0 parts per billion (∼1,300 ng/g lipid) [8]. In addition, the 24-year follow-up study of the Yucheng cohort exposed to PCBs and furans in poisoned rice oil in 1974 showed that, in women diagnosed with chloracne and thus exposed to a high level of pollutant, the OR for diabetes was 5.5 (95% CI 2.3-13.4) and that for hypertension 3.5 (1.7-7.2) as compared with those who were chloracne-free [34].…”
Section: Discussionmentioning
confidence: 99%
“…The Michigan PBB study (25 years of follow-up) showed increased incidence of diabetes in individuals with a PCB level >10.0 parts per billion (∼1,300 ng/g lipid) [8]. In addition, the 24-year follow-up study of the Yucheng cohort exposed to PCBs and furans in poisoned rice oil in 1974 showed that, in women diagnosed with chloracne and thus exposed to a high level of pollutant, the OR for diabetes was 5.5 (95% CI 2.3-13.4) and that for hypertension 3.5 (1.7-7.2) as compared with those who were chloracne-free [34].…”
Section: Discussionmentioning
confidence: 99%
“…US Air Force veterans from the Vietnam war [6,16], dioxin-exposed individuals following the Seveso accident [17], and populations living nearby [18] or working at [19] industrial plants producing dioxin-containing pesticides or herbicides. Apart from dioxin, other environmental pollutants have been epidemiologically associated with type 2 diabetes, as summarised in Table 1 [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] (reviewed in [6]). …”
Section: Epidemiological Evidencementioning
confidence: 99%
“…PCDD/Fs are nonpolar, poorly water-soluble, lipophilic, stable chemicals that are produced as byproducts and released into the environment in ultra-trace amounts from various combustion processes. PCDD/Fs is a class of endocrine disrupting chemicals to induce several adverse health effects including disruption of steroid sex hormones , delay growth and thyroid function (Su et al, 2010), interference with human reproduction (Chao et al, 2007;Su et al, 2012), increase internal dose of the breastfed infants (Chao et al, 2004;, and increment of diabetes or cancer incidences (Wang et al, 2008). The levels of atmospheric PCDD/Fs depend on human industrial and domestic activities.…”
Section: Introductionmentioning
confidence: 99%